Conflicts in co-design: engaging with tangible artefacts in multi-stakeholder collaboration. Issue 4 (2nd October 2021) - Andersen, Pernille Viktoria Kathja; Mosleh, Wafa Said
ABSTRACT: This article explores how engagement with tangible design artefacts can invite, and sustain focus on, the different professional perspectives that emerge in multi-stakeholder workshops. Multiple interests and intentions can pose challenges, especially in the initial phases of collaborative work. Existing design research emphasises the use of tangible artefacts as mediators for collaboration, but limited attention has been given to how they could be used to expose tensions and opposing perspectives as a way to enable movement beyond stuck conversation among stakeholders. We examine the design and use of two tangible artefacts for multi-stakeholder collaborative inquiry, demonstrating how interaction with them can encourage open and active confrontation of underlying and contradictory stakeholder interests and intentions. Since unspoken conflicts can undermine the early stages of collaborative inquiry, we propose that the use of tangible artefacts to explore taken-for-granted assumptions is crucial if stakeholders are to negotiate perspectives and co-create new meaning.